Effects of swainsonine on rat liver and kidney: biochemical and morphological studies (The Rockefeller University Press, 1985)
Among the reported effects of the plant toxin swainsonine in animals are a decreased level of Golgi mannosidase II activity, an increase in lysosomal alpha-D-mannosidase activity, oligosaccharide accumulation, vacuolization of cells, and neurological changes. We now find that, in the rat, the alkaloid rapidly induces vacuolization of both liver and kidney cells, but oligosaccharides accumulate only in the latter. We demonstrate by enzyme- and immunocytochemistry that the induced pleomorphic vacuoles are lysosomal in nature. The vacuoles do not appear to be derived from the Golgi apparatus, which retains its typical ultrastructural appearance, but are formed by autophagy. In swainsonine-fed rats, the lysosomal system is highly developed in hepatocytes, Kupffer cells, and cells of the proximal convoluted tubules. The relation of this hypertrophy of the lysosomal system to the known effects of swainsonine on glycoprotein biosynthesis and on Golgi and lysosomal alpha-mannosidases is not clear. In addition, in liver there occurs a marked increase in mitotic figures in the hepatocytes. This occurred in the absence of both cell death and increased liver size as estimated by gross morphology.